Justice and ethics in tourism - Jamal, Tazim (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"This is the first book to look at justice and ethics in tourism in one volume, bringing theoretical perspectives into conversation with tourism, development and the environment. The book explores some key ethical perspectives and approaches to justice, including building capabilities, distributive justice, recognition, representation and democracy. Human rights, integral in the context of tourism, are discussed throughout. Space is also given to structurally embedded injustices (including those related to historical racism and colonialism), responsibility towards justice, justice within and beyond borders, and justice in the context of sustainability, governance, policy, and planning. A variety of international case studies contributed by experts from around the globe illustrate these concepts and facilitate understanding and practical application. Comprehensive and accessible, this is essential reading for tourism students and researchers and will be of interest to students of geography, development studies, business and hospitality management, cultural studies, international relations and environmental studies. The range of insights offered make this a valuable reading for planners, policy makers, business managers and civil society organizations as well"--
The landscape of travel and tourism -- Equity and justice -- Diversity and recognition -- Responsibility and care -- Sustainability and conservation -- Democracy and governance -- Towards good and just tourism.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Moral and ethical aspects; Tourism -- Social aspects; BUSINESS & ECONOMICS / Business Ethics